Comparing different scoring systems for predicting mortality risk in preterm infants: a systematic review and network meta-analysis - Zeng, Zhaolan; Shi, Zeyao; Li, Xiaowen (Frontiers in Pediatrics, 2023)
Background: This study aimed to compare the predictive values of eight scoring systems (Neonatal Critical Illness Score [NCIS], Neonatal Therapeutical Intervention Score System [NTISS], Clinical Risk Index for Babies [CRIB], Clinical Risk Index for Babies II [CRIB-II], Score for Neonatal Acute Physiology Perinatal Extension [SNAPPE], Score for Neonatal Acute Physiology Perinatal Extension II [SNAPPE-II], Score for Neonatal Acute Physiology [SNAP], and Score for Neonatal Acute Physiology II [SNAP-II]) for the mortality risk among preterm infants. Methods: The Embase, PubMed, Chinese Biomedical Database, Web of Science, and Cochrane Library databases were searched to collect studies that compared different scoring systems in predicting the mortality risk in preterm infants from database inception to March 2023. Literature screening, data extraction, and bias risk assessment were independently conducted by two researchers. Subsequently, the random-effects model was used for the network meta-analysis. Results: A total of 19 articles were included, comprising 14,377 preterm infants and 8 scoring systems. Compared to CRIB-II, NCIS, NTISS, SNAP-Ⅱ, and SNAPPE-II, CRIB demonstrated better predictive efficiency for preterm infant mortality risk (P<0.05). Relative to CRIB, CRIB-II, and SNAPPE, SNAP-Ⅱ had worse predictive efficiency for preterm infant mortality risk (P<0.05). The surface under the cumulative ranking curve of the eight scoring systems was as follows: CRIB (0.980) > SNAPPE (0.718) > SNAP (0.534) > CRIB-Ⅱ (0.525) > NTISS (0.478) > NCIS (0.422) > SNAPPE-Ⅱ (0.298) > SNAP-Ⅱ (0.046). Conclusion: The CRIB scoring system showed the highest accuracy in predicting preterm infant mortality risk and was simple to perform. Therefore, CRIB selection can be prioritized in clinical practice.